PERANCANGAN KEMASAN RENDANG TELUR ROSDIANA DI KOTA - MAHDIANSYAH, Eliya Pebriyeni, S.Pd., M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
This final work is to get traditional food packaging that has been updated to be interisting and can add a new target audience. Through packaging design it is hoped that this business can have a visual identity application that is able to attract the attention of the consumer audience so that in the future it can reach a wider target market.This design uses visual communication theory design, media, typography color and layout. Data collection begins with observation, interviews and documentation. Furthermore, the data analysis method used is SWOT (Strenght, Weaknes, Oportuninty, Treatment)This design produces packaging in the form of a rectangular box. Besides the main media also equipped by several media such as posters, X banners, t-shirts, stickers, pins, calendars and id cards.Kata kunci : Desain Kemasan, Promosi, Rendang Telur Rosdiana